STUDY ON MACROZOOBENTHOS COMMUNITY IN THE WATERS OF THE RIVER AIR PERIKAN MUNICIPALITY OF PAGAR ALAM SOUTH SUMATRA - Tampubolon, Rafles; Hanafiah, Zazili; Junaidi, Endri (BIOVALENTIA: Biological Research Journal, 2017)
The research entitled â€œ Study on Macrozoobenthos Community in the Waters of the River Air Perikan Pagar Alam Municipalityâ€, was conducted from November 2007 until March 2008. The aims of the research: to know about composition, density, diversity index, dominancy index, and similarity index, which based on the different microhabitat types. Sampling was carried out on November 2007. Five sampling stations were determined by survey methodÂ  and the Purposive Sampling method was used at each sampling point to find stony, gravel, sandy and leaf pack area as a different microhabitat substrate. Twenty one orders (Ephemeroptera, Trichoptera, Diptera, Plecoptera, Collembola, Hemiptera, Odonata, Coleoptera, Lepidoptera, Megaloptera, Hymenoptera, Orthoptera, Decapoda, Plesiopora, Tricladida, Amphipoda, Isopoda, Mesogastropoda, Ctenobranchiata, Eulamellibranchiata, and Rhynchobdellida) which are consisted of 70 families and 151 genera were identified from four types of substrates on each sampling station. According to this research, station 4 has the highest in composition (80 genera), and the lowest one at station 1(33 genera). The highest abundance was 12589 ind./m2Â  found in the station 5, and the lowest one was in the station 1 approximately 880 ind./m2. For the diversity index value, station 3 was the highest (3.1) and the lowest one was station 5 (1.9). The Dominancy index was found in station 5 at the sandy substrates wasÂ  approximately 0,8 index, which dominated by Tubifex sp. There were Â differences species compositionÂ  on each station.Â Keywords : Macrozoobenthos, community, the river Air Perikan.